A CORRELATIONAL STUDY ON THE REFERENCES AND THE STUDENTS’ READING COMPREHENSION - Cenderato , S.Pd, M.Pd (Universitas Kapuas, 2018)
This research is a study on the correlation between the students’ ability in using reference words and the students’ reading comprehension of the second semester of FISIP UnkaSintangin academic year 2017/2018.The method of this research was a correlational Study. The subject of the research was 32 students.The technique of data collecting was measurement and the tool of collecting data was a test in form of a multiple choice. From the computation, it can be concluded that the correlation between the students’ score performance on test 1 and their performance on test 2 is significant. The correlation occurred at r (coefficient correlation) = 0, 51 and the value of t-test (4.14) higher than the value of t-table (2, 048). In other words, the correlation between the students’ ability in using references and the students’ reading comprehension of the second semester of FISIP Unka Sintang is significant.